2000
DOI: 10.1046/j.1365-2249.2000.01090.x
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular adhesion molecule-1 (ICAM-1) deficiency protects mice against severe forms of experimentally induced colitis

Abstract: SUMMARYICAM-1 (CD54), the ligand for LFA-1 and Mac-1, is up-regulated during inflammatory reaction on the activated vascular endothelium. To determine its role in intestinal inflammation, we induced acute experimental colitis in mice with a deleted ICAM-1 gene, by feeding them with 3% dextran sodium sulphate (DSS) in drinking water for 7 days. Chronic colitis was elicited by DSS similarly, followed by 2 weeks with water. In the acute phase of inflammation, ICAM-1-deficient mice exhibited a significantly lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 34 publications
4
53
1
Order By: Relevance
“…We have also reported that loss of all ␤ 2 -integrins in DSS colitis results in severely decreased leukocyte recruitment and disease pathology with a concomitant reduction in vascular density accenting the role of increased leukocyte recruitment in pathological angiogenesis during experimental colitis (1,31). Moreover, Bendjelloul et al (14) found that ICAM-1 Ϫ/Ϫ mice are protected in DSS-induced colitis, providing further evidence for the importance of this molecule in IBD. VCAM-1, which binds ␣ 4 ␤ 1 and members of the ␤ 2 integrin family, is present on endothelium typically upon activation (expression induced by inflammatory cytokines) and is involved in the slow rolling of monocytes and lymphocytes during inflammatory cell recruitment.…”
Section: Angiogenic Mediators In Ibd and Experimental Colitissupporting
confidence: 54%
“…We have also reported that loss of all ␤ 2 -integrins in DSS colitis results in severely decreased leukocyte recruitment and disease pathology with a concomitant reduction in vascular density accenting the role of increased leukocyte recruitment in pathological angiogenesis during experimental colitis (1,31). Moreover, Bendjelloul et al (14) found that ICAM-1 Ϫ/Ϫ mice are protected in DSS-induced colitis, providing further evidence for the importance of this molecule in IBD. VCAM-1, which binds ␣ 4 ␤ 1 and members of the ␤ 2 integrin family, is present on endothelium typically upon activation (expression induced by inflammatory cytokines) and is involved in the slow rolling of monocytes and lymphocytes during inflammatory cell recruitment.…”
Section: Angiogenic Mediators In Ibd and Experimental Colitissupporting
confidence: 54%
“…ICAM-1 is a cell-surface protein that is induced first on the endothelium of the submucosal blood vessels and whose expression precedes surface ulceration (46). It is thought to play a role in recruiting effector immune cells to the mucosa and in establishing the inflammatory process (47,48). To determine whether the IRE1β mutation acts early in the sequence of events that lead to chronic colitis, we compared the ICAM-1 staining in DSS treated IRE1β -/-and IRE1β +/-mice.…”
Section: Resultsmentioning
confidence: 99%
“…Our results also showed that ICAM-1 expression was increased from 6h to 6 days after a dose of 22.5 Gy irradiation to the colon. Enhancement of ICAM-1 expression has been reported in Crohn's disease 11) , ulcerative colitis 12) , DSS-induced colitis 13) , and trinitrobenzene sulfonic acid (TNBS)-induced colitis 14) . However, some other studies have shown unchanged expression in human IBD and TNBS-induced colitis 31) .…”
Section: Discussionmentioning
confidence: 99%
“…ICAM-1 expression on endothelium plays an important role in migration of activated leukocytes into the sites of inflammation 10) . Increased expression of ICAM-1 in the colon of patients with inflammatory bowel disease (IBD) has been reported [11][12][13][14] . Recent studies have shown that ICAM-1 expression can be induced by ionizing radiation 15,16) .…”
Section: Introductionmentioning
confidence: 99%